Evaluation of the Arabic Curricullum Implementation at PTKAIS - Natsir, Muhammad (Asalibuna, 2023)
KKNI (Indonesian National Qualifications Framework) as a basis for strengthening competitive competencies at the global level. In particular, strengthening Arabic language competence is oriented towards responding to the socio-religious reality of society, as well as responding to realities in a global context. And this has implications for strengthening the curriculum with the character of local wisdom and is varied. This research includes applied research with qualitative and quantitative approaches, using an evaluative descriptive design. This research aims to; 1) describe the system for evaluating the implementation of the PBA curriculum at PTKAIS throughout the Pati Residency, namely Unisnu Jepara and IP. MAFA. Starch. 2) analyze and describe the evaluation of the implementation of the PBA PTKAIS Curriculum throughout the Pati Residency, using the CIPP evaluation model (context, input, process, product). The results showed that the model for evaluating the implementation of the PBA PTKAIS Curriculum throughout the Pati Residency was formulated using the CIPP model based on the IQF. The results of the PBA PTKAIS evaluation using the CIPP evaluation model show good average results for all components and indicators in the CIPP model, namely; context, input, process, product components. The follow-up of the evaluation results is to recommend improving the curriculum and learning system in the technical and non technical domains.